Heterosis of seedling traits and their correlation to aphids infestation in chili pepper. Issue 1 (February 2020) - Daryanto, A; Hidayat, P; Maharijaya, A; M Syukur, dan
Abstract: Chili pepper is a vegetable plant in a group of horticulture plants. The seedling vigorous and their genetic potency to reduce the number of aphids infestation can encourage chili pepper productivity. The objective of this research was to study heterosis, heterobeltiosis, and correlation of seedling traits to aphids infestation from ten chili hybrid genotypes derived from five chili inbred lines through half diallel crosses. The experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications at the IPB University experiment field and laboratory, Darmaga. Seedling traits and aphids infestation observed at 5 weeks after sowing. Two aphids were infested per plant and evaluated 12 days after infestation. Heterosis effects were predicted based on the average values of their parents whereas heterobeltiosis were predicted based on the average values of the best parents. Hybrid IPB C5 x IPB C4 had the highest heterosis and heterobeltiosis for all seedling traits. Hybrid IPB C3 x IPB C4, IPB C4 x IPB C313 and IPB C20 x IPB C313 had the highest heterosis and heterobeltiosis for reducing number aphids per leaf and aphids per plant. There was no correlation between seedling traits with aphids infestation.